Why mosquitoes buzz in people's ears eaudiobook - Aardema, Verna (Weston Woods, 1994)
"In this Caldecott Medal winner, Mosquito tells a story that causes a jungle disaster. ""Elegance has become the Dillons' hallmark . . . An impressive showpiece."-Booklist, starred review." Set in the African jungle, a mosquito whispers a lie into an iguana's ear. The iguana, not wanting to listen, plugs his ears with sticks. With his ears plugged, he is unable to hear the python, causing the python to react. An unfortunate chain of events involving several other jungle animals occur as a result.